2019
DOI: 10.1007/s12451-019-00220-z
|View full text |Cite
|
Sign up to set email alerts
|

De effectiviteit van Eigen Kracht-conferenties in de jeugdzorg

Abstract: Op 15 mei 2019 verdedigde Sharon Dijkstra haar proefschrift, getiteld Balancing the scale of responsibility: The effectiveness of family group conferencing in child welfare. Vijf jaar lang hebben de auteurs, in samenwerking met de Eigen Kracht Centrale en Jeugdbescherming Regio Amsterdam, onderzoek gedaan naar de effectiviteit van Eigen Kracht-conferenties bij gezinnen betrokken bij Jeugdbescherming Regio Amsterdam. Dit artikel geeft een overzicht van de belangrijkste onderzoeksresultaten. Het jeugdzorgbeleid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…With regard to FGC, knowledge on moderators of effectiveness is scarce, and results of the few available studies are inconsistent. For instance, whereas Sheets et al (2009) showed greater effectiveness of FGC for ethnic minority families in terms of family reunification, other studies found that FGC resulted in more extended supervision orders and re-referrals to child welfare in minority families when compared to ethnic majority (native) families (Dijkstra et al, 2016b; Hollinshead et al, 2017). To examine which families benefit most from the FGC approach, we studied several family characteristics that may moderate its effectiveness, including ethnicity, family situation, education level of parents, parental intellectual disability, and referral reason.…”
mentioning
confidence: 96%
“…With regard to FGC, knowledge on moderators of effectiveness is scarce, and results of the few available studies are inconsistent. For instance, whereas Sheets et al (2009) showed greater effectiveness of FGC for ethnic minority families in terms of family reunification, other studies found that FGC resulted in more extended supervision orders and re-referrals to child welfare in minority families when compared to ethnic majority (native) families (Dijkstra et al, 2016b; Hollinshead et al, 2017). To examine which families benefit most from the FGC approach, we studied several family characteristics that may moderate its effectiveness, including ethnicity, family situation, education level of parents, parental intellectual disability, and referral reason.…”
mentioning
confidence: 96%